Lambda and Antiambda production in central Pb-Pb collisions at 40, 80, and 158A GeV - Antičić, Tome; Baatar, B.; Barna, D. Bartke, J.; Behler, M. Betev, L.; Bialkowska, H. Billimeier, A.; Blume, C. Boimska, B.; Botje, M. Bracinik, J.; Bramm, R. Brun, R.; Buncic, P. Cerny, V.; Christakoglou, P. Chvala, O.; Cramer, J.G. Csato, P.; Darmenov, N. Dimitrov, A.; et al. (2004)
Production of Lambda and Antilambda hyperons was measured in central Pb-Pb collisions at 40, 80, and 158 A GeV beam energy on a fixed target. Transverse mass spectra and rapidity distributions are given for all three energies. The Lambda/pi ratio at mid-rapidity and in full phase space shows a pronounced maximum between the highest AGS and 40 A GeV SPS energies, whereas the Antilambda/pi ratio exhibits a monotonic increase.
Projekt MZOS
ENG